Answer:
Answer:
x = 3.3
EF = 31.1
FG = 21.7
Step-by-step explanation:
Step-by-step explanation:
Simplifying
9 + -2x = 35
Solving
9 + -2x = 35
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9' to each side of the equation.
9 + -9 + -2x = 35 + -9
Combine like terms: 9 + -9 = 0
0 + -2x = 35 + -9
-2x = 35 + -9
Combine like terms: 35 + -9 = 26
-2x = 26
Divide each side by '-2'.
x = -13
Simplifying
x = -13
Answer:
What happens if you put a booger on a tissue. The tissue starts to boogey dance.
Step-by-step explanation:
Answer:
51
Step-by-step explanation:
8.5/1
and
x/6
cross multiply
51=x
Answer:
21,000
Step-by-step explanation:
This is more of straightforward multiplication, so I cannot explain much! If you want me to try to do more, then just comment.
(7 * 10 * 5) * (3 * 10 * 2)
= (70 * 5) * (30 * 2)
= (350) * (60)
= 21,000
Thusly, in standard form, the equation given is
.
Hope this helps! (: